Anlotinib enhances the antitumor activity of radiofrequency ablation on lung squamous cell carcinoma. (February 2021) - Zhou, Wei; Gao, Yongping; Tong, Yaqi; Wu, Qingjun; Zhou, Yunzhi; Li, Yanming
Graphical abstract: Abstract: Anlotinib is a novel molecular targeted drug that has been approved for the treatment of lung adenocarcinoma. Currently these agents are rarely used in the treatment of lung squamous cell carcinoma (LSCC). Bronchoscope-guided radiofrequency ablation (RFA) is a new strategy proposed for the treatment of LSCC that is able to alleviate the obstruction of the respiratory tract caused by LSCC by direct destruction of the tumor tissues. The presence work aims to reveal whether Anlotinib could enhance the antitumor activity of RFA on LSCC cells. The results from real-time PCR (qPCR) confirmed overexpression of targets of anlotinib activity, including receptor tyrosine kinase or the MPAK/PI3K-AKT pathway kinases, in LSCC tissues. Treatment with anlotinib inhibited the survival, in vitro invasion, and migration of LSCC cells. Moreover, the antitumor effects of RFA were investigated using a rodent model of LSCC. The combination of RFA and anlotinib treatment enhanced the antitumor effect of RFA treatment. We propose a combinative strategy of RFA and anlotinib as a novel approach for successful management of LSCC.